What makes practice perfect? How tertiary piano students self-regulate play and non-play strategies for performance success. (March 2022) - Suzuki, Akiho; Mitchell, Helen F
Self-regulated practice is critical to musicians' development, but it is unclear what components of practice contribute to performance quality. This study aimed to explore tertiary music students' practice using performance evaluations as indicators of practice efficacy. Five tertiary piano students prepared a quick study task of two pieces for a mock performance, in 2 hours over 2 days. An expert panel evaluated the mock performances and performers were ranked accordingly. Practice session recordings and interview transcripts were analysed according to the three phases of Self-Regulated Learning (forethought, performance, self-reflection) and linked to the pianists' final performance evaluations. Successful pianists planned their practice and set interpretative goals, while their less successful peers practiced reactively without planning. The highest-ranked pianist's self-regulation was facilitated by non-play practice which involved taking long pauses and using strategies such as score study, mark score, and listen to own recording. The lowest-ranked pianist failed to identify problems or self-evaluate effectively. Future studies should explore the use and content of non-play practice strategies, especially self-recording, to empower music students to develop and self-regulate their practice. The quick study task provided an effective practice assessment tool and could be used to diagnose and track practice approaches.